1970
DOI: 10.1159/000121924
|View full text |Cite
|
Sign up to set email alerts
|

Localization and Specificity of Corticosteroid “Feedback Receptors” at the Hypothalamo-Hypophyseal Level; Comparative Effects of Various Steroids Implanted in the Median Eminence or the Anterior Pituitary of the Rat

Abstract: In order to elucidate the localization and specificity of corticosteroid feedback receptors in the hypothalamo-hypophyseal system, various steroids were implanted in the median eminence and the anterior pituitary of female rats and their effects on stress-induced ACTH release were investigated. Suppression of ACTH release was observed after the implantation of dexamethasone, cortisol, corticosterone, 11-dehydro-corticosterone and 11-deoxycorticosterone (DOC) in the anterior median eminence. 11-Deoxycortisol (R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

1973
1973
2009
2009

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 1 publication
1
5
0
Order By: Relevance
“…We have now shown that the CRF response of the hypothalamus to acetylcholine is altered by adrenalectomy and replacement therapy with corticosterone thus confirming our previous findings on the effect of electrical stimulation (Bradbury et al 1974). Our data, taken in conjunction with experi¬ ments on the implantation of corticosteroids in the hypothalamus (Smelik & Sawyer, 1962;Bohus & Strashimirov, 1970), lead us to conclude that this negative feedback effect of corticosteroids on the hypothalamus is of physiological significance.…”
Section: Discussionsupporting
confidence: 88%
“…We have now shown that the CRF response of the hypothalamus to acetylcholine is altered by adrenalectomy and replacement therapy with corticosterone thus confirming our previous findings on the effect of electrical stimulation (Bradbury et al 1974). Our data, taken in conjunction with experi¬ ments on the implantation of corticosteroids in the hypothalamus (Smelik & Sawyer, 1962;Bohus & Strashimirov, 1970), lead us to conclude that this negative feedback effect of corticosteroids on the hypothalamus is of physiological significance.…”
Section: Discussionsupporting
confidence: 88%
“…However, the degree of inhibition of both parameters by cortisone was much less than that produced by dexamethasone. This compares with the relative potency of the two corticoids in the feedback suppression of ACTH release (30). The apparent differences in the effectiveness of the antagonism of estrogen-stimulated responses in the uterus by glucocorticoids and some sex steroids according to duration of pretreatment suggests possible differences in the mechanism(s) of inhibition or differing susceptibility to various steroid antagonists at similar points of inhibition.…”
Section: Discussionmentioning
confidence: 92%
“…For example, adrenalectomy (ADX) results in higher PVN neuropeptide synthesis and secretion both at the basal and stressed states. Additionally, feedback can occur either directly at the level of the CRH and AVP neurons of the PVN as well as the corticotrophs of the anterior pituitary, or indirectly though GR and MR containing brain regions that project to the PVN such as the hippocampus and amygdala (Davidson and Feldman, 1967; Bohus and Strashimirov, 1970; Dallman et al, 1987; Sawchenko, 1987). Glucocorticoid effects vary according to duration of exposure.…”
Section: Discussionmentioning
confidence: 99%